Pandangan dan Kontribusi Islam terhadap Perkembangan Sains - Nasrul Fauzi; Ibnu Chudzaifah (Al-Fikr: Jurnal Pendidikan Islam, 2019)
Islam acts for its adherents to conduct studies on the behavior or forms of circulation and changes that occur, both in the context of the universe and those that occur between fellow humans, as well as the development of modern technology. In connection with this understanding, the requested discussion of Islam, the words requested by the Prophet Muhammad, required compulsory knowledge for Muslims. Islam contributes to science between other verses in the Qur'an which encourages Muslims to develop science. Islam through the Qur'an is the basis of epistemology and ideology for Muslim scientists who connect their attitudes and relationships to transcendence with the creator. Expect that there is a spiritual dimension in dzikir and fear for Allah. Muslim appreciation of the amazing knowledge of the early days of Islam. At this time Muslims were able to play a role and master various disciplines. Islamic Ummah has a very prominent role but has differences in politics and internal crises in involving thinking, the role of Muslims is declining and very alarming. The role of Islam in the development of science and technology adds there are two namely First, making Islamic Aqeedah a paradigm of science. The paradigm that represents Muslims, is not a secular paradigm as it is now. Second, making Islamic Islam (born from Islamic Aqeedah) as a standard for the use of science and technology in everyday life.